2006
DOI: 10.1038/sj.pcan.4500924
|View full text |Cite
|
Sign up to set email alerts
|

The association between body size, prostate volume and prostate-specific antigen

Abstract: Increasing prostate volume contributes to urinary tract symptoms and may obscure prostate cancer detection. We investigated the association between obesity and prostate volume, prostate-specific antigen (PSA) and PSA density among 753 men referred for prostate biopsy. Among men with a negative biopsy, prostate volume significantly increased approximately 25% from the lowest to highest body mass index (BMI), waist or hip circumference or height categories. PSA was 0.7 ng/ml lower with a high waist-to-hip ratio.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 29 publications
5
55
0
1
Order By: Relevance
“…48 Several studies also have reported hyperinsulenemia or the metabolic syndrome associated with higher PSA levels, but this was believed to be mediated through the effects of obesity and insulin on increased prostate volume and benign prostatic hyperplasia. [50][51][52][53] Thus, while the mechanisms linking C-peptide or HbA1c to PSA requires further investigation, the observed inverse relationships in this study are generally consistent with the previously reported inverse relationship between testosterone and insulin.…”
Section: Discussionsupporting
confidence: 91%
“…48 Several studies also have reported hyperinsulenemia or the metabolic syndrome associated with higher PSA levels, but this was believed to be mediated through the effects of obesity and insulin on increased prostate volume and benign prostatic hyperplasia. [50][51][52][53] Thus, while the mechanisms linking C-peptide or HbA1c to PSA requires further investigation, the observed inverse relationships in this study are generally consistent with the previously reported inverse relationship between testosterone and insulin.…”
Section: Discussionsupporting
confidence: 91%
“…25,26 In the current study, age had a negative association with BMI. This finding is compatible with the National Nutrition Survey of Japan 1956-2005, which reported that the BMI in men increased with age by birth cohort, but decreased with crosssectional age.…”
Section: Discussionmentioning
confidence: 87%
“…biopsy core † 14 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) 16 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) 14 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) 14 (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) 14 …”
Section: <00001unclassified
“…In addition, the mechanism through which DM and prostate cancer are related has not been fully elucidated. Men with DM are known to generally have lower prostate-specific antigen (PSA) level but larger prostate size than others not having DM (Hammarsten and Hogstedt, 2001;Berger et al, 2005;Werny et al, 2006;Fowke et al, 2007;Turgutalp et al, 2013). Also, it can be suggested that the reported protective effect of DM may be due to the differences in PCa screening among diabetic and non-diabetic patients.…”
Section: Introductionmentioning
confidence: 99%